2017
DOI: 10.4103/jrms.jrms_316_17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nepeta bracteata Benth. on allergic rhinitis symptoms: A randomized double-blind clinical trial

Abstract: Background:Allergic rhinitis (AR) is one of the health problems in the world. It is necessary to develop new treatment procedure for control of this disease. The aim of this study was to assess the effect of Zofa (Nepeta bracteata Benth) on AR patients.Materials and Methods:In this double-blind randomized clinical trial study, 71 patients (37 patients in treatment and 34 in placebo group) participated. In treatment group, N. bracteata syrup (NBS) was used for 4 weeks as three times a day. The efficacy of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…[1] Allergic Rhinitis (AR) as the most common allergic diseases has an ascending prevalence worldwide[23] that annually billion dollars paid for the treatment of physical and mental problems and disabilities of such patients that imposes a heavy burden on health services. [45] General principles of treatment are education and awareness, the avoidance of allergen, appropriate medicine use, and finally the immunotherapy application. [678] Given that complete allergen avoidance is not possible and administrations of current medicines are restricted because of their side effects and also decreased effectiveness following continuous consumption.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Allergic Rhinitis (AR) as the most common allergic diseases has an ascending prevalence worldwide[23] that annually billion dollars paid for the treatment of physical and mental problems and disabilities of such patients that imposes a heavy burden on health services. [45] General principles of treatment are education and awareness, the avoidance of allergen, appropriate medicine use, and finally the immunotherapy application. [678] Given that complete allergen avoidance is not possible and administrations of current medicines are restricted because of their side effects and also decreased effectiveness following continuous consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Reporting bias was considered to be high in six studies (20.7%) [ 28 , 35 , 39 , 42 , 43 , 46 ] where these studies did not report baseline data of the participants and/or relevant clinical outcome(s) of allergic rhinitis. Other biases were considered to be unclear in 16 studies (55.2%) [ 25 , 27 , 28 , 31 , 34 43 , 46 , 48 ] due to unclear funding source or were industry-sponsored, conducted, or authored trials. The remaining three with unclear risk for other biases were cross-over studies.…”
Section: Resultsmentioning
confidence: 99%
“…Rhinorrhoea . Pooled estimates from six studies [ 27 , 28 , 30 , 31 , 42 , 48 ] showed that medicinal plants may have no effect on rhinorrhoea (SMD -0.85, 95% CI -1.73 to 0.04; participants = 399; studies = 6; I 2 = 94%). The evidence is very uncertain.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of the phenolics content in the hydroalcoholic extract of the R. damascena preparation was determined via the spectrophotometric method and the Folin-Ciocalteu's reagent, NaHCO 3 solution, and gallic acid as the standard (23,24). Then, the content of phenolics in the extracts was expressed in terms of gallic acid equivalent (mg of GA/g of extract).…”
Section: Total Phenolic and Flavonoid Content Assaymentioning
confidence: 99%
“…Then, the content of phenolics in the extracts was expressed in terms of gallic acid equivalent (mg of GA/g of extract). Further, the spectrophotometry method via AlCl3 solution and the catechin standard was conducted for the flavonoid content (24,25). The content of flavonoids in the extracts was expressed in terms of the catechin equivalent (mg of CAT/g of the extract).…”
Section: Total Phenolic and Flavonoid Content Assaymentioning
confidence: 99%